A RELAÇÃO DE VALORES DE POTENCIAIS CONSUMIDORES DE CURSOS DE GRADUAÇÃO - Samuel Carvalho De Benedicto; Aline Michelli Penido da Silva; Luiz Henrique de Barros Vilas Boas; Cândido Ferreira da Silva Filho (Revista Gestão Universitária na América Latina, 2012)
Nowadays, the Higher Learning Institutions (IES) face great competitivity, they search a new positioning on market. The understanding of the consumer profile enables the development of positioning strategies for new products/services. Thus, it is necessary to understand the variables which need to be improved in order to make the corporate image of the organization and the satisfaction of the entrant and students with the offered education services better. This work was intended to identify the relationship of the values of potential consumers of undergraduate courses when of the choice of an IES. In-depth interviews utilizing the qualitative technique laddering, were performed which make use of the theoretical presupposed ones of the mean and purpose chains. A hierarquical value map (MHV) was constructed, which allows to identify the dominant chains which influence the consumer’s behavior in his purchasing decision. The results show the consumers’ concern about the IES which present a set of essential attributes which allow a place in the labor market and reach a range of personal aspirations. The clients/consumers investigated long for IES which possess: recognition of the society, qualified professors; high quality teaching; practical classes in specialized laboratories. Such attributes lead to diverse desirable consequences to the consumers of the education services in higher learning: the broadening of the knowledge of the student; the increase of the chances to get a job; the safety in profession practice; the conquest of the so-dreamt financial independence. Such attributes and consequences are linked to several values such as pleasure, safety, self-fulfillment, happiness, solidarity and independence/liberty.